High Prevalence of Multi-drug Resistant Methicillin-Resistant Staphylococcus aureus in Tertiary Egyptian Hospitals - Abdel-Aty E Alfeky; Mahmoud M Tawfick; Mohamed S Ashour; Abdel-Nasser A El-Moghazy (Journal of Infection in Developing Countries)
Introduction: Methicillin-resistant Staphylococcus aureus (MRSA) is an emerging cause of morbidity and mortality worldwide. This work aimed to study the occurrence of multidrug-resistant MRSA (MDR-MRSA) in tertiary Egyptian hospitals and determine the antimicrobial susceptibilities and the genetic relatedness of isolates for epidemiological assessment.